Motivation and Readiness for Physical Activity and Exercise Behaviour among People with Chronic Musculoskeletal Pain: A Brief Report. Issue 1 (30th July 2018) - Brooks, Jessica M.; Costigan, Kelly; Wu, Jia-Rung; Chen, Xiangli; Bengtson, Kevin; Chan, Fong; Iwanaga, Kanako; Chiu, Chungyi
Abstract : The main objective of this study was to investigate the relationships between motivation and readiness levels for physical activity and exercise behaviour among persons with chronic musculoskeletal pain. Participants were 211 U.S. adults with chronic musculoskeletal pain from online support groups as well as specialty and primary care clinics (females = 86.7%; mean age = 43.4 years, SD = 14.4 years). The participants completed an online survey on their engagement in physical activity and exercise behaviour. Multiple one-way analyses of variance with post-hoc comparisons using the Tukey HSD test revealed significant differences between the readiness stages of change groups of preintenders, intenders, and actors in their motivation for physical activity and exercise behaviour. Specifically, the actor group of behavioural change reported higher levels of motivation beliefs for physical activity and exercise behaviour compared to preintenders and intenders. These findings suggest that people with chronic musculoskeletal pain experiencing increased motivation for physical activity and exercise behaviour are more engaged in desired behaviours than the persons with chronic pain reporting varying degrees of behavioural intentions.